2021
DOI: 10.1007/s00405-021-06965-5
|View full text |Cite
|
Sign up to set email alerts
|

Suprameatal–transzygomatic root endoscopic approach to the geniculate ganglion: an anatomical and radiological study

Abstract: Suprameataltrans-zygomatic root endoscopic approach to the geniculate ganglion: an anatomical and radiological study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, the problem with this approach is that the space for drilling is small compared with the approach from the retroauricular incision to the mastoid. Cadaveric examination revealed that the geniculate ganglion could be identified via the route from Shambaugh's incision to the upper tympanic cavity by scraping the zygomatic bone in front of the ear canal (9). PEES type A is similar to this approach; moreover, we determined that the approach developed in cadaver research in a previous report is possible to be performed in clinical cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the problem with this approach is that the space for drilling is small compared with the approach from the retroauricular incision to the mastoid. Cadaveric examination revealed that the geniculate ganglion could be identified via the route from Shambaugh's incision to the upper tympanic cavity by scraping the zygomatic bone in front of the ear canal (9). PEES type A is similar to this approach; moreover, we determined that the approach developed in cadaver research in a previous report is possible to be performed in clinical cases.…”
Section: Discussionmentioning
confidence: 99%
“…The approaches utilized for facial nerve decompression (FND) include the trans mastoid, middle cranial fossa, and trans labyrinthine approaches depending on the site of injury and hearing status ( Fernandez et al., 2021 ). The middle cranial fossa approach has been used for nerve decompression in patients with serviceable hearing and those whose affected area span from the geniculate ganglion (GG) and labyrinthine segment to metal portion of the facial nerve ( Aslan et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%